2023
DOI: 10.1021/acs.macromol.3c00830
|View full text |Cite
|
Sign up to set email alerts
|

Thiourea-Based Bifunctional Catalysts for Epoxide-Involved Ring-Opening Polymerization of α-Amino Acid N-Carboxyanhydrides

Abstract: Thiourea-quaternary ammonium salt bifunctional catalysts with both electrophilic and nucleophilic centers were designed in this paper to initiate the ring-opening polymerization (ROP) of α-amino acid N-carboxyanhydrides (NCAs) for the efficient synthesis of polypeptides. We disclosed this kind of bifunctional catalyst for the efficient synthesis of polypeptides in the presence of propylene oxide (PO), which was judiciously added as an in situ activator for the efficient ROP of NCA. By MALDI-TOF MS and 1H NMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recent elegant works demonstrated that hydroxyl groups with an assistance of H-bonding interactions could successfully initiate NCA polymerizations as well. , These inspiring results motivated us to explore the traditional organobase/alcohol combinations that have been used widely in ROP of lactone. As expected, they could also smoothly promote the NCA polymerizations at room temperature (entries 7–8, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent elegant works demonstrated that hydroxyl groups with an assistance of H-bonding interactions could successfully initiate NCA polymerizations as well. , These inspiring results motivated us to explore the traditional organobase/alcohol combinations that have been used widely in ROP of lactone. As expected, they could also smoothly promote the NCA polymerizations at room temperature (entries 7–8, Table ).…”
Section: Resultsmentioning
confidence: 99%